A framework to support the identification of critical habitat for wide-ranging species at risk under climate change - Lionel Leston; Francisco V. Dénes; Teegan D. S. Docherty; Junior A. Tremblay; Yan Boulanger; Steven L. Van Wilgenburg; Diana Stralberg; Peter Sólymos; Samuel Haché; Kathy St. Laurent; Russ Weeber; Bruno Drolet; et al. (Biodiversity and Conservation, 2024)
To recover species at risk, it is necessary to identify habitat critical to their recovery. Challenges for species with large ranges (thousands of square kilometres) include delineating management unit boundaries within which habitat use differs from other units, along with assessing any differences among units in amounts of and threats to habitat over time. We developed a reproducible framework to support identification of critical habitat for wide-ranging species at risk. The framework (i) reviews species distribution and life history; (ii) delineates management units across the range; (iii) evaluates and compares current and (iv) potential future habitat and population size and (v) prioritizes areas within management units based on current and future conditions under various scenarios of climate change and land-use. We used Canada Warbler ( Cardellina canadensis ) and Wood Thrush ( Hylocichla mustelina ) in Canada as case studies. Using geographically weighted regression models and cluster analysis to measure spatial variation in model coefficients, we found geographic differences in habitat association only for Canada Warbler. Using other models to predict current habitat amount for each species in different management units, then future habitat amount under land use and climate change, we projected that: (1) Canada Warbler populations would decrease in Alberta but increase in Nova Scotia and (2) Wood Thrush populations would increase under most scenarios run in Quebec, New Brunswick and Nova Scotia, but not in Ontario. By comparing results from future scenarios and spatial prioritization exercises, our framework supports identification of critical habitat in ways that incorporate climate and land-use projections.